Educating for Unknowable Futures: The United Nation Relief and Works Agency-led Education for Palestinian Refugees in Jordan - Alstadnes Malme, Julie (Critical Education, 2026)
Proponents of critical pedagogy aim to liberate oppressed populations through emancipatory forms of praxis (Darder et al., 2017). This article draws on this pedagogy, in particular Freirean pedagogy, to explore refugee education offered by The United Nations Relief and Works Agency for Palestine refugees in the Near East (UNRWA). Drawing on interviews with UNRWA teachers and other educational staff, alongside document analysis, this paper examines how UNRWA in Jordan enact its mandate. In particular, the article focuses on a policy program, ‘Human Rights, Conflict Resolution and Tolerance (HRCRT)’ that UNRWA implements in their education. With an analysis shaped by core aspects of a Freirean pedagogy, the paper argues that the HRCRT program creates authentic possibilities for advancing Palestinian liberation. Despite the unknown future for both the Agency and the Palestinian refugees, findings from the interviews and other data materials reflected a shared consciousness of the purpose of the UNRWA-led education for Palestinian refugees, which is in accordance with both UNRWA’s mandate and fundamental principles within Freirean pedagogy.